2011
DOI: 10.3164/jcbn.10-108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of half-solid nutrient for the elderly patients with percutaneous endoscopic gastrostomy

Abstract: Percutaneous endoscopic gastrostomy tube feeding is widely used for patients with swallowing dysfunction and a history of repeated aspiration pneumonitis. However, liquid nutrient feeding via percutaneous endoscopic gastrostomy is not effective enough to prevent aspiration pneumonitis and related inflammatory responses. We performed this prospective multi-centre study to clarify the efficacy of half-solidification of nutrients to prevent fever possibly caused by aspiration pneumonitis in elderly patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…That may be due to differences in the dynamic viscosity of semi-solid feed used in various studies. A recent study also demonstrated that use of semi-solid feed was associated with fewer observational days with fever but the cause of fever in that study was not clearly defined 20. …”
Section: Discussionmentioning
confidence: 91%
“…That may be due to differences in the dynamic viscosity of semi-solid feed used in various studies. A recent study also demonstrated that use of semi-solid feed was associated with fewer observational days with fever but the cause of fever in that study was not clearly defined 20. …”
Section: Discussionmentioning
confidence: 91%
“…After screening 912 records, 39 potentially relevant studies were identified ( Figure 1 ). Fifteen of these 39 studies met the study inclusion criteria (Muramatsu et al, 2018 [ 17 ]; Ishii et al, 2006 [ 18 ]; Togashi & Paku 2012 [ 19 ]; Paku et al, 2012 [ 20 ]; Nakahori et al, 2011 [ 21 ]; Abe et al, 2011 [ 22 ]; Muramatsu et al, 2010 [ 23 ]; Kanie et al, 2004 [ 11 ]; Shizuku et al, 2011 [ 24 ]; Nagasawa 2009 [ 25 ]; Toh et al, 2016 [ 26 ]; Tabei et al, 2018 [ 27 ]; Nishiwaki et al, 2009 [ 12 ]; Shimizu et al, 2016 [ 13 ]; Higashiguchi et al, 2014 [ 28 ]). The 15 studies comprised 10 RCTs [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 ] and five crossover trials [ 11 , 12 , 13 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…ETF was administered via a gastrostomy tube in 15 studies; in one of these studies, ETF was delivered via a nasogastric tube in some patients [ 12 ]. In these 15 studies, 33.3–100% of patients had stroke [ 11 , 12 , 13 , 17 , 24 , 25 , 26 , 27 , 28 ], 20.0–60.0% had dementia [ 11 , 12 , 17 , 25 , 26 , 27 ], 46.1% had respiratory disorders [ 26 ], 18.5% had dysphagia [ 17 ], 15.3% had neurodegenerative disorders [ 26 ], 13.7% had malignancy [ 26 ], 6.7% had neuromuscular disorders [ 12 ], 7.4% had hypoxic encephalopathy [ 27 ], 7.4% had esophageal cancer [ 27 ], 3.7% had gastric cancer [ 27 ], 3.7% had brain tumor surgery [ 27 ], 3.7% had cerebral contusion [ 27 ], and 3.7% had disuse syndrome [ 27 ]. Comorbidities were as follows: 12.1–25.6% had diabetes mellitus [ 13 , 26 ], 3.4–86.4% had hiatal hernia [ 12 , 13 , 26 ], 40% had reflux esophagitis [ 12 ], 10.6% had pneumoperitoneum [ 13 ], 4.5% had gastric bleeding [ 13 ], and 2.6% had partial gastric resection [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of GER was significantly reduced in patients who received semi-solid compared to liquid nutrients, however this effect did not appear to be mediated by differences in gastric emptying time. Shizuku et al similarly studied 42 adult patients with PEG tubes [50]. These patients received 8 weeks of feeding with a liquid diet and 8 weeks of feeding with a semi-solid diet.…”
Section: Management Of Oropharyngeal Dysphagia With Aspirationmentioning
confidence: 99%